Cannabinoid toxicity in pediatrics. Issue 2 (April 2019) - Blohm, Eike; Sell, Peter; Neavyn, Mark
Abstract : Purpose of review: The advent of legalized cannabis in multiple regions of the United States has rendered the drug more accessible to pediatric patients. Pediatricians and Pediatric Emergency Medicine Providers face new challenges in counseling both patients and their parents, diagnosing exploratory ingestions of cannabinoids in toddlers, and managing complications of prolonged, heavy cannabis use in adolescents. The purpose of this review article is to provide clinicians a succinct summary of recent literature regarding tetrahydrocannabinol (THC) pharmacokinetics, pharmacodynamics, impacts on development, as well as presentations of acute and chronic toxicity. Recent findings: Many young children being admitted to the hospital for cannabis toxicity have been exposed to high concentration products, such as edibles, resins, or vaping fluid. These products contain extremely high concentrations of cannabinoids, and lead to sedation, respiratory depression, and other adverse effects. Chronic toxicity associated with cannabis consumption includes neurocognitive changes and cannabinoid hyperemesis syndrome. Summary: Clinicians should provide guidance for pediatric patients and their caregivers to reduce the risk of accidental cannabis exposure, particularly with high concentration products. In addition, clinicians should consider chronic cannabis exposure when evaluating certain complaints, such as chronic vomiting or educational performance at school.